ANALISIS PELAKSANAAN SAMSAT DRIVE THRU DI UPT PENGELOLAAN PENDAPATAN PEKANBARU KOTA - Dailiati, Surya; Hernimawati, Hernimawati; Sudaryanto, Sudaryanto; Novanadila, Iva (Komunitas Manajemen Kompetitif, 2024)
Motor vehicle tax payments are made at the Riau Province Regional Revenue Agency (BAPENDA) through the Revenue Management Technical Implementation Unit (UPT). This Revenue Management UPT was previously known as SAMSAT (One-Stop Single Administration System). The problems are long queues, lack of outreach about services and slow systems or device glitches. According to Ripley & Franklin in Aslinda (2022), the success of policy implementation is influenced by the level of compliance, the size of the routine and the desired impact. These three factors influence the policies made in public services, especially for the implementation of Samsat Drive Thru. The research was conducted at the Pekanbaru Revenue Management UPT Office, Regional Revenue Agency, Riau Province, Jl Gajah Mada, Simpang Empat District, Pekanbaru District, Pekanbaru City. The sources in this research are: State Civil Apparatus and the community. The sources and types of data in this research are primary and secondary data. Data analysis was carried out descriptively qualitatively. As a result, the Pekanbaru City Regional Revenue Agency, especially the Revenue Management Technical Implementation Unit (UPT), has implemented the Drive Thru Samsat well. Existing problems are overcome by means such as increasing capacity in the form of increasing the number of counters or officers to speed up the service process.